HUBUNGAN PENGETAHUAN DAN SIKAP MAHASISWA BARU PRODI S1 KESEHATAN MASYARAKAT TERHADAP PENCEGAHAN SEKS PRANIKAH DI UNIVERSITAS PAHLAWAN TUANKU TAMBUSAI - ZURRAHMI Z.R; PUTRI EKA SUDIARTI; RIZKI RAHMAWATI LESTARI (Jurnal Ners, 2022)
Free sex among Indonesian teenagers is currently very worrying. Many factors related to the prevention of premarital sexual behavior in adolescents, including the knowledge and attitudes of adolescents. The purpose of this study was to determine the relationship between knowledge and attitudes of new students in the Public Health Study Program towards the prevention of premarital sex at Pahlawan Tuanku Tambusai University. This type of research is analytic with cross sectional design. The population in this study were all new students of the S1 Public Health study program at Pahlawan Tuanku Tambusai University, totaling 68 people using the Total Sampling technique. The data collection tool uses a questionnaire. Data analysis in this study used univariate and bivariate analysis with chi square test. The results of the study using the chi square test showed that most of the respondents had less knowledge about the prevention of premarital sex, most of the respondents were negative about the prevention of premarital sex, there was a relationship between knowledge and prevention of premarital sex, new students of the S1 Public Health study program at Pahlawan Tuanku Tambusai University with a p value 0.001, there is a relationship between attitude and prevention of premarital sex for new students from the Public Health Study Program at Pahlawan Tuanku Tambusai University with a p value of 0.004. Parents are expected to be able to better guide and monitor the association of young women and provide knowledge about sex education to their children.